SAT0382 Changes in volumetric bone mineral density and bone microarchitecture in patients with ankylosing spondylitis. a five-year prospective study using hrpqct. (15th June 2017) - Deminger, A; Klingberg, E; Lorentzon, M; Carlsten, H; Jacobsson, LT; Forsblad-d'Elia, H
Abstract : Background: Studies have demonstrated increased prevalence of osteoporosis in patients with ankylosing spondylitis (AS) in the hip and lumbar spine assessed by conventional DXA but the peripheral skeleton is less studied. The peripheral skeleton can be studied in detail by high-resolution peripheral quantitative computed tomography (HRpQCT) demonstrating data of the volumetric bone mineral density (vBMD) and bone microarchitecture. We have previously shown that patients with AS from Western Sweden had lower vBMD measured by HRpQCT in radius and tibia compared with healthy controls [1]. No prospective study in this matter has been published in AS. Objectives: To investigate changes over 5 years in the peripheral vBMD and microarchitecture in patients with AS. Methods: HRpQCT of ultra-distal radius and tibia was performed in male AS-patients (NY criteria) at baseline and at the five-year follow-up. The patients were also assessed with blood samples and questionnaires. Results: Of the 69 patients included at baseline 57 (83%) patients were re-examined at the five-year follow-up. Baseline characteristics of the 57 patients [median (IQR)]: age 48 (35 to 61) years, symptom duration 21 (11 to 34) years, ESR 10 (5 to 17) mm/h, CRP 3 (1 to 7), ASDASCRP 1.8 (1.3 to 2.8) and BASDAI 2.3 (1.2 to 4.2). 23% used TNF-inhibitors, 75% used NSAIDs and 2% bisphosphonates. All measurements at tibia had good quality and matched images had common regions ≥80%. The images of radius of 12 patients had to be excluded due to insufficient quality. At tibia, the total, cortical and trabecular vBMD decreased significantly. In the microarchitecture an increase in the trabecular separation was seen (Table). Changes in vBMD were negatively and significantly correlated; Spearman's correlation coefficient between -0.3 and -0.4, to Δ-values (difference between follow-up and baseline) for ESR, CRP (cortical vBMD), ASDASCRP (total vBMD and cortical vBMD) and BASDAI (total vBMD). At radius, no significant change in vBMD was observed; however, less power for analyses of radius. An increase was seen in the cortical thickness and the trabecular number while the trabecular thickness decreased (Table). Changes in cortical vBMD was negatively and significantly correlated, r ≈ -0.3, to Δ-CRP and Δ-ASDASCRP . Conclusions: Over five years, this group of male patients with AS decreased in the vBMD of tibia, both trabecular and cortical. Even though there were alterations in the microarchitecture, no significant change in vBMD of radius was seen. Increases in inflammatory markers and disease activity had a negative impact on the cortical vBMD. The differences in the development of vBMD and microarchitecture in loaded and unloaded skeleton as well as factors associated with the changes needs to be further investigated. References: Klingberg, E., et al., Bone microarchitecture in ankylosing spondylitis and the association with bone mineral density, fractures, and syndesmophytes. Arthritis Res Ther, 2013. 15: p. R179. Disclosure of Interest: None declared